Workplace disability diversity and job-related well-being in Britain: a WERS2004 based analysis - Getinet A. Haile (Institute for the Study of Labor (IZA), 2009)
This paper attempts to establish empirically whether there is a link between workplace disability and employee job-related well-being. Using nationally representative linked employer-employee data for Britain, I employ alternative econometric techniques to account for unobserved workplace heterogeneity. I find that workplace disability diversity is associated with lower employee well-being among people with no reported disability. Tests conducted also indicate that workplace equality policies do not ameliorate this effect.
urn:nbn:de:101:1-20090304488
Keywords: J14; J82; J7; I31; 330; Disability diversity; job-related well-being; linked employer-employee data; Britain; Arbeitsplatz; Behinderte Arbeitskräfte; Arbeitszufriedenheit; Großbritannien